Initiation of Experimental Temporal Lobe Epilepsy by Early Astrocyte Uncoupling Is Independent of TGFβR1/ALK5 Signaling - Henning, Lukas; Steinhäuser, Christian; Bedner, Peter (Frontiers in Neurology, 2021)
Blood–brain barrier (BBB) dysfunction following brain insults has been associated with the development and progression of focal epilepsy, although the underlying molecular mechanisms are not fully elucidated yet. Activation of transforming growth factor beta (TGFβ) signaling in astrocytes by extravasated albumin impairs the ability of astrocytes to properly interact with neurons, eventually leading to epileptiform activity. We used the unilateral intracortical kainate mouse model of temporal lobe epilepsy (TLE) with hippocampal sclerosis (HS) to gain further insights into the role of BBB leakage in status epilepticus (SE)-induced epileptogenesis. Immunohistochemical examination revealed pronounced albumin extravasation already 4 h after SE induction. Astrocytes were virtually devoid of albumin immunoreactivity (IR), indicating the lack of uptake by this time point. Inhibition of the TGFβ pathway by the specific TGFβ receptor 1 (TGFβR1) kinase inhibitor IPW-5371 did not prevent seizure-induced reduction of astrocytic gap junction coupling. Thus, loss of coupling, which is thought to play a causative role in triggering TLE-HS, is most likely not mediated by extravasated albumin. Continuous telemetric EEG recordings and video monitoring performed over a period of 4 weeks after epilepsy induction revealed that inhibition of the TGFβ pathway during the initial phase of epileptogenesis slightly attenuated acute and chronic epileptiform activity, but did not reduce the extent of HS. Together, these data indicate that albumin extravasation due to increased BBB permeability and TGFβ pathway activation during the first hours after SE induction are not significantly involved in initiating TLE.